Interaction between Internet Browsing Habit and Dyspepsia Syndrome in Adolescent - Bayupurnama, Putut; Sofia, Noor Asyiqah; Cahyani, Angelin Utami (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Background: There were many patients, including adolescent, with dyspepsia symptoms in our daily clinical practice have been interacting with internet search engine to find medical information which induced or worsened their dyspeptic symptoms. Aim of the study is to know  the pattern of   internet browsing habit and dyspepsia syndrome in adolescentMethod: Grade 12 level students of senior high schools in Yogyakarta, Indonesia were included in the study with stratified random sampling method. Students with confirmed organic dyspepsia diagnosis were excluded. We use two simple questions to reveal the students internet browsing habit, question no 1 :“Did you ever browse information about diseases in the internet?” (answer choice: a.never;b.once;c.more than once); question no 2.: “Did you ever browse information about your medical complaint in the internet?” (answer choice: a.never;b.once;c.more than once). We used validated Gastrointestinal Symptom score (GIS) to reveal the students dyspepsia symptoms. Data were analyzed with chi-square test and anova.Results: There were 665 (477 girls and 188 boys) senior high school students (age range : 16-20 years old) included in this study. Based on question no 1, the result  showed significantly different (p 0.001) between students with  and without the dyspepsia syndrome, and the question no 2 also showed similar result (p=0.002). The anova between GIS and question no 1 showed significantly different ( p0.001) and the similar result was also found between GIS and question no 2 (p0.001). Conclusion:The internet browsing habit may influence the development of dyspepsia syndrome in adolescent and further study is needed to find the cause and effect relationship.